Written Margin and Fees in Akad Salam Online: Comparative Fiqh Analysis with Empirical Philosophical and Juridical Approaches - Madani, Farid; Nurhikmah, Aulia; Jubaedah , Dedah; Setiawan, Iwan (Zona Law And Public Administration Indonesia, 2025)
The development of digital technology has given birth to the practice of online-based salam contracts that are different from conventional salam contracts, especially in the determination and transparency of margin fees. This difference raises the issue of fiqh muamalah and consumer protection, especially related to the potential for gharar and inequality in the position of the parties. This research aims to analyze philosophically, comparative fiqhi, and empirical juridical margin fees in online and offline salam contracts and their implications for consumer protection. The research method used is normative-empirical law with philosophical approaches, school comparisons, and empirical juridical approaches. Normative data is sourced from classical and contemporary fiqh literature, DSN-MUI fatwas, and consumer protection regulations, while empirical data is obtained from the study of the practice of salam contracts on digital platforms. The results of the study show that the margin fee in the salam contract is in principle allowed as ujrah for the services of intermediaries as long as it is clearly agreed from the beginning of the contract and separated from the price of the goods. However, the practice of online greetings still shows low transparency of margin fees and the use of standard clauses that have the potential to harm consumers